The mediating role of corporate governance on intellectual capital and corporate performance - Earnest, Dewi Fariha (2013)
Recognition and development of intellectual capital (IC) as organizational invaluable intangible asset has been traced as immense vital essence that influence good corporate performance and success. This paper attempts to synthesize relevant empirical research and literature to extend the intended potentials of IC on corporate performance, particularly in publicly traded companies. The paper also proposes that corporate governance poses a mediating role between IC and corporate performance by linking the resource based view theory (RBV) and agency theory in its relationship. Since the existing literature provides less evidence that attempt to observe the influence of IC when integrated with the effectiveness of a separate function in an organization, this paper offers and calls a promising proposition for future research.